Current challenges and future prospect of biomass cooking and heating stoves in Asian Countries - Ahmad, Riaz; Ilyas, Hafiza Nabila; Li, Bin; Sultan, Muhammad; Amjad, Muhammad; Aleem, Muhammad; Abbas, Adnan; Imran, Muhammad Ali; Riaz, Fahid (Frontiers in Energy Research, 2022)
The utilization of biomass for cooking and heating is as old as the early stage of human evolution because of its availability. In Asia, the major portion of the population is dependent on solid biomass for cooking and heating applications. Biomass cookstove produces emissions like carbon monoxide (CO), particulate matter with aerodynamic diameter ≤ 2.5 μm (PM2.5) which are dependent on its classifications and characteristics of fuel used in stoves. These emissions trigger many health risks because of utilization of traditional cookstoves (TCS) having less thermal efficiency. The literature contains a considerable amount of information on biomass cookstoves; however, it is dispersed particularly for Asian countries. In this principle, this paper gives an overview of available literature on the biomass cookstoves for cooking and heating in the Asian countries which are involving Bangladesh, China, India, Mongolia, Nepal, Pakistan, Sri Lanka, and Lao People's Democratic Republic (PDR). This paper covers a detailed discussion on various aspects of biomass cookstove: history, classification, fuel characteristics, health risks, design criteria, scenario in selected Asian countries, thermal efficiency and emission comparison, and barriers to dissemination of improved biomass cookstoves (ICS). Learning from the review and comparison made conclude that the ICS has better thermal efficiency, and lesser emissions as well as health risks but have some potential barriers to dissemination.